(untitled) (JURNAL HUKUM DAS SOLLEN, 2021)
Recognition and protection of indigenous peoples has been stated in various laws and regulations, but implicitly does not regulate the form of traditional rights or elements of indigenous peoples. The existence of the rights of the Niowula indigenous people in Ende Regency has been increasingly eroded by various government policies that have robbed the existence of the rights of indigenous peoples around the Kelimutu National Park (TNK). due to the establishment of special zoning for conservation areas at the expense of cultivated land (agriculture and coffee plantations covering an area of ​​approximately 35 hectares) belonging to the customary law community of Niowula Village, Detusoko District, which existed long before the existence of Kelimutu National Park. The government, in this case the Kelimutu National Park, tends to use and enforce state laws in the name of the interests of national development, while on the other hand, indigenous peoples who are supposed to control and have the right to manage natural resources in their own territories as a source of livelihood and economic resources are neglected. The problem in this research is what legal regulations can be used as the basis for the community in managing the conservation area (TNK) of Ende Regency. The method used in this research is normative legal research, with a statute approach. The result of the research is that there is a conflict between the indigenous peoples of Niowula, Ende Regency and (TNK) regarding the zoning of a conservation area which has sacrificed an area of ​​approximately 35 hectares of cultivated land belonging to the indigenous people of Niowula Village, Detusoko District. Meanwhile, the Constitutional Court Decision 35 / PUU-X / 2012, has changed the status and legal position of customary forests, from what was originally "customary forest is state forest to" customary forest is forest within the territory of customary law communities ". The Constitutional Court’s decision restores the rights of indigenous peoples to manage their customary forests.